Bilateral Ovarian Krukenberg Tumor in a Full-Term Pregnancy. (24th October 2010) - Dueñas-García, Omar Felipe; Diaz-Sotomayor, Maricela; Chanana, Charu
Abstract : Objective . Krukenberg tumors in pregnancy are very rare and their management can present a dilemma for the obstetrician gynecologist. Case Report . We present the case of a G3P2002 who presented to us and the 38 weeks gestation with bilateral massive Krukenberg tumors. Despite at surgery and chemotherapy she died 3 months postpartum. Conclusion . Early detection followed by surgery and chemotherapy could possibly result in a favorable outcome with such patients.